Imported inflation ... concept, transmission channels, effects, and processors Iraq Case study for the period (1990-2015) - الكبيسي, محمد صالح; مثنى, تحسين محمود (Journal of Economics and Administrative Sciences, 2019)
This research aims to explain the effect of the imported inflation (which moves through the raise of global prices to Iraqi economy) over local prices, besides, the recognition the most important channels of imported inflation moving, its causes, effects, ways and policies that reduce the negative effects. To achieve the research aim, the deductive approach was adopted through using descriptive method to describe and determine phenomenon. The most important conclusion is that the research found out that there are two channels to transmission imported inflation in world. The first channel is the direct channel (prices) and the second channel is the indirect (income). The most important recommendation is to create sovereign fund (Oil fund) for the aim of absorbing surplus of unrefined oil revenues and decreasing entering the imported inflation that created by indirect channel.